2015
DOI: 10.1016/j.jad.2015.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Validation studies of the Edinburgh Postnatal Depression Scale for the antenatal period

Abstract: Background: Relatively few studies have focused on the validation of psychometric scales

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
180
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(189 citation statements)
references
References 73 publications
5
180
0
4
Order By: Relevance
“…As such, we can only evaluate elevated depressive symptoms and cannot determine whether these associations hold true for clinically diagnosed depression. Additionally, there may be different cut points to best distinguish high versus low depressive symptoms depending on timing of administration, as well as sociodemographic and contextual characteristics (4043). However, among validation studies of the English version of the EPDS using the standard cut point of 13 or higher for postpartum depression, sensitivity ranged from 76 to 100% and specificity ranged from 70 to 99% (41).…”
Section: Discussionmentioning
confidence: 99%
“…As such, we can only evaluate elevated depressive symptoms and cannot determine whether these associations hold true for clinically diagnosed depression. Additionally, there may be different cut points to best distinguish high versus low depressive symptoms depending on timing of administration, as well as sociodemographic and contextual characteristics (4043). However, among validation studies of the English version of the EPDS using the standard cut point of 13 or higher for postpartum depression, sensitivity ranged from 76 to 100% and specificity ranged from 70 to 99% (41).…”
Section: Discussionmentioning
confidence: 99%
“…The EPDS is the most widely used self-report questionnaire to screen PPD (27), and various cutoff scores have been used in different studies (21, 28, 29). The current study used the cutoff score of 9 or more, based on one study which investigated the reliability and validity of the EPDS among women in the postnatal and control groups in Japan, and showed that sensitivity is 75% and specificity is 93% when using the cutoff score of 9 or more (30).…”
Section: Methodsmentioning
confidence: 99%
“…s. Garcia-Esteve, Ascaso, Ojuel, & Navarro, 2003). The EPDS is a 10-item instrument widely used to assess depression post-delivery and has also been shown to be valid during the prenatal period (Kozinszky & Dudas, 2015). Responses are based on a 4-point scale (0, 1, 2, and 3) and responses are summed to produce a total score, with a maximum score of 30.…”
Section: Methodsmentioning
confidence: 99%